Artistic Heritage of A. A. Plastov as a Visual Source on the History of the Collective Farm Village of the Period of Stalinism - O. R. Khasyanov; P. S. Kabytov; L. N. Galimova (Научный диалог, 2019)
The possibility of using visual sources in the reconstruction of everyday practices of the collective farm peasantry during the Stalinism is analyzed. According to the authors, the visual turn that occurred in socio-humanitarian knowledge in the last quarter of the twentieth century, sets the task of studying everyday practices, the value world and mental attitudes of various social subjects. They believe that without involving visual sources from the period of Stalin's Soviet modernization, it is impossible to reconstruct the objective picture of the “social life world” of the collective farm village during the period of large-scale social and economic transformations. On the example of the fine heritage of A. A. Plastov, one of the most respected Soviet artists working in line with Soviet socialist realism, various aspects of the everyday life of the Soviet collective farm village are reconstructed. The study is aimed at solving a number of issues of the agrarian and social history of Russia, which until now have not attracted proper research attention. It is noted that Soviet visual sources served as the basis for the construction of a new Soviet civic identity and a means of discipline of social subjects. Attraction along with visual sources of information extracted from traditional written sources (archival documents and materials of periodicals) allows to ensure the reliability and verification of the results.